Anaerobic–aerobic system for beverage effluent treatment : performance evaluation and microbial community dynamics - Tyagi, Vinay Kumar (2020)
A novel ‘anaerobic filter’ with a pulsing bio-cord bed, the anaerobic pulsed bed filter (APBF), was integrated with the aerobic sequencing batch reactor (aeSBR) to treat effluent from a beverage manufacturer. The APBF reactor achieved 61% COD and 70% BOD removal at 8 h HRT and 5.45 kg COD/m3.d OLR. The combined APBF-aeSBR system achieved COD, BOD, TSS and TN removals of 97%, 98%, 80% and 82%, respectively. Notwithstanding the APBF's immobilized biomass, it was suspected the range of loadings could cause changes in the microbial community. 16S rRNA high throughput sequencing analysis of the immobilized biomass showed Euryarchaeota (7.60%–44.42%), Proteobacteria (4.65%–37.98%), Bacteroidetes (9.72%–27.13%), Firmicutes (8.39%–22.69%) and Synergistetes (0.73%–13.20%) were the dominant phyla. At genus level, Acinetobacter, Streptococcus, Cloacibacillus, Methanobacterium, Methanothrix and Methanospirillum were observed to be dominant.